NLRC5, a promising new entry in tumor immunology. Issue 1 (19th July 2016) - Chelbi, Sonia T.; Guarda, Greta
Abstract : The recent use of T cell-based cancer immunotherapies, such as adoptive T-cell transfer and checkpoint blockade, yields increasing clinical benefit to patients with different cancer types. However, decrease of MHC class I expression is a common mechanism transformed cells take advantage of to evade CD8 + T cell-mediated antitumor responses, negatively impacting on the outcome of immunotherapies. Hence, there is an urgent need to develop novel approaches to overcome this limitation. NLRC5 has been recently described as a key transcriptional regulator controlling expression of MHC class I molecules. In this commentary, we summarize and put into perspective a study by Rodriguez and colleagues recently published in Oncoimmunology, addressing the role of NLRC5 in melanoma. The authors demonstrate that NLRC5 overexpression in B16 melanoma allows to recover MHC class I expression, rising tumor immunogenicity and counteracting immune evasion. Possible ways of manipulating NLRC5 activity in tumors will be discussed. Highlighting the therapeutic potential of modulating NLRC5 levels, this publication also encourages evaluation of NLRC5, and by extension MHC class I pathway, as clinical biomarker to select personalized immunotherapeutic strategies.